A Step‐by‐Step Multiple Stimuli‐Responsive Nanoplatform for Enhancing Combined Chemo‐Photodynamic Therapy. Issue 12 (27th January 2017) - Wang, Yi; Wei, Guoqing; Zhang, Xiaobin; Xu, Funeng; Xiong, Xiang; Zhou, Shaobing
Abstract : A robust and smart protoporphyrin‐based polymer nanoplatform, which is capable of successively recognizing the variation of biological signals and reacting with them in a dynamic mode, is successfully developed. It combines the chemotherapy and photodynamic therapy in a same system, leading to a high treatment outcome while a low adverse side effect of therapeutic agent.